Fluid Retention Syndrome (FRS) - a review - Zamanu, GKMS; Hossain, A; Mondol, BA; Hossain, SS; Deb, SR (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13246 J. Dhaka Med. Coll. 2012; 21(1): 97-108